What is antimicrobial stewardship?. (November 2017) - Dyar, O.J.; Huttner, B.; Schouten, J.; Pulcini, C.; ,
Abstract: Background: The use of the term 'antimicrobial stewardship' has grown exponentially in recent years, typically referring to programmes and interventions that aim to optimize antimicrobial use. Although antimicrobial stewardship originated within human healthcare, it is increasingly applied in broader contexts including animal health and One Health. As the use of the term 'antimicrobial stewardship' becomes more common, it is important to consider what antimicrobial stewardship is, as well as what it is not. Aims: To review the emergence and evolution of the term 'antimicrobial stewardship'. Sources: We searched and reviewed existing literature and official documents, which mostly focused on antibiotics. We contacted the authors of the first publications that mentioned antimicrobial stewardship. Content: We describe the historical background behind how antimicrobial stewardship came into use in clinical settings. We discuss challenges emerging from the varied descriptions of antimicrobial stewardship in the literature, including an over-emphasis on individual prescriptions, an under-emphasis on the societal implications of antimicrobial use, and language translation problems. Implications: To help address these challenges, we suggest viewing antimicrobial stewardship as a strategy, a coherent set of actions which promote using antimicrobials responsibly. We stress the continuous need for 'responsible use' to be defined and translated into context-specific and time-specific actions. Furthermore, we present examples of actions that can be undertaken within antimicrobial stewardship across human and animal health.